STUDI PENGEMBANGAN OBJEK DAYA TARIK WISATA KAWASAN EKOWISATA GUNUNG API PURBA NGLANGGERAN, KABUPATEN GUNUNGKIDUL, D. I. YOGYAKARTA - , Niskan Walid Masruri ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Nglanggeran Ancient Volcano Ecotourism Area (KE-GAPN) has an area of 48 Ha (118,61 acre) offering scenic view of ancient rocky mountain rich in flora and fauna which is protected by a management. The tourism area management is run by the Nglanggeran Area local government. The development of KE-GAPN ecotourism is implemented as an effort to support the conservation comprehensively. The study is aimed at identifying the management of the area, the Tourism Attraction Object (ODTW) potential, and then identifying the tourist and local people perception toward the ODTW, as well as organizing the ongoing development strategy for the ODTW KE-GAPN. The method steps applied in the study are (1) calculating the rate of ODTW KE-GAPN